DESAIN LKPD BERORIENTASI KOMPLEKSITAS KONTEN DAN PROSES KOGNITIF PADA MATERI VEKTOR UNTUK PEMBELAJARAN FISIKA SMA/MA - Vindy Hifarianti; Amali Putra; Syafriani Syafriani (Universitas Negeri Padang, 2017)
This study is based on the background that in physics learning teaching materials in the form of Student’s Worksheet (LKPD) is necessary, so that learning is not inclined to the teacher-centered. In addition, the students’ competence is still low in terms of levels of cognitive processes can be improved through the use of LKPD. This study aims to produce the products such as oriented LKPD complexity of content and cognitive processes in the material vectors, also to know the quality of LKPD terms of validity and practicality. This study is the research and development using the 4D model. This model consists of 4 stages, such as define stage, design stage, develop stage, and disseminate stage. However, in this study the 4D model reduced to 3D, so the study was only done to develop stage. The subjects of the study consist of three lecturers from the Physics Department, FMIPA UNP as a validators and 2 Physics teachers SMAN 10 Padang as validators and practitioners. Data were analyzed by using qualitative and quantitative analysis. Based on the research that has been conducted, it was resulted the LKPD oriented complexity of content and cognitive processes. Product research is categorized as very valid aspects LKPD requirements, aspects of the complexity of the content in LKPD, aspects of the complexity level of cognitive processes in LKPD, and aspects of learning model components the guided inquiry in LKPD with an average values of 81.8. Product research is also categorized as very practical by teachers with average values of 84.6 from the aspect of completeness, scope, presentation, benefits, and opportunities implementation of LKPD